EVALUASI FUNGSI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEGAWAI PUSKESMAS KECAMATAN LOPOK - Kamal, Afina Aurellya; Karmeli, Elly; Wulandari, Alifiah Putri (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to determine the effect of human resource management in improving employees performance at Public Health Centre in Lopok Sub-District. The type of this study was associative study. The type of data used was quantitative data obtained directly from primary sources using a research instrument in the form of a questionnaire. The sample that will be used as respondents in this study was 55 employee at Public Health Centre in Lopok Sub-District who were determined using non-probability sampling techniques with the simple random sampling method. Data analysis tools were performed using multiple linear regression analysis techniques, t test, F test, and the coefficient of determination (R2) test. The results of this study showed that human resource management consisting of performance assessment, career development and compensation had a positive and significant effect on the employees performance at Public Health Centre in Lopok Sub-District, both partially and simultaneously. The variation of changes in the value of the employee performance at Public Health Centre in Lopok Sub-District can be explained by the performance assessment, career development and compensation variables, which was 67.6%, while the remaining of 32.4% was explained by other variables that are not included in this study, such as work motivation, work enthusiasm and welfare.